Multidisciplinariedad del derecho corporativo en México - Morales Ozuna, Enrique Eriberto (2023)
The central point of the study is to briefly explain the process of creating a commercial company with a multidisciplinary perspective of corporate law in Mexico, as an integrating axis of the legal disciplines consisting of Commercial, Notarial, Tax, Labor and Law. of Social Security. The significance of the proposal lies in exposing from a multidisciplinary perspective each legal system that affects the correct creation of a corporation in Mexico, making visible the points of concurrence of each of the legal sections of these legal dis ciplines, which apparently do not have correlation, given the nature of each of them; however, their meeting point is to bring a company into legal life. This being the final concordant or common objective of these various areas of law and, of course, the activities that corporations could subsequently develop, until their liquidation.